PENGARUH KEPUASAN KERJA DAN MOTIVASI TERHADAP KINERJA KARYAWAN GIANT SUPERMARKET CABANG MANGGARAI - Wimpy Mulia (Universitas Mercu Buana, 2013)
Abstract: Hypotheses proposed are (1) there is positive and significant impact on thejob satisfaction with employee performance Giant Supermarket Main BranchManggarai: (2) there is positive and significant impact on work motivation withemployee performance Giant Supermarket Main Branch Manggarai: and (3) there ispositive and significant impact does simultaneously on job satisfaction and workmotivation with employee performance Giant Supermarket Main Branch Manggarai.This suggests that higher job satisfaction and work motivation, the higher theemployee performance.Empirically note that job satisfaction and work motivationplays an important role in improving the employee performance on Giant Main BranchManggarai. Therefore, the results of this study expected to be reference to improveemployee performance by taking into account the level of job satisfaction and workmotivation.Keywords: Job Satisfaction, Work Motivation, Employee Performance